The implementation of monetary policy in Canada - Walter Engert; Toni Gravelle; Donna Howard (Bank of Canada, 2008)
The authors present a detailed discussion of the Bank of Canadas' framework for the implementation of monetary policy. As background, they provide a brief overview of the financial system in Canada, including a discussion of the financial services industry and the money market. Key features of the large-value payments system, which is integral to the implementation of monetary policy, are also explained. The authors then discuss in some detail the operating framework for the implementation of monetary policy. An assessment of the effectiveness of the Bank of Canadas' framework is also provided, including an analysis of monetary policy implementation in the period of financial market stress beginning in August 2007.
Keywords: E52; E58; G21; 330; Financial institutions; Financial markets; Monetary policy implementation; Payment; clearing; and settlement systems; Zentralbank; Bankensystem; Bankenpolitik; Zahlungsverkehr; Verrechnungsverkehr; Geldpolitik; Kanada